Earnings Management in JII Firms: Does Audit Quality Moderate CSR, Ownership, and Leverage? - Salfa Nurul Tafziyah; Nawirah Nawirah (Politeknik Ganesha Medan, 2026)
The existence of earnings management practices remains a phenomenon among companies listed in the Jakarta Islamic Index (JII). This condition indicates that the presentation of financial information does not fully reflect actual performance, potentially affecting the quality of decisions made by stakeholders. The purpose of this study is to examine the effect of corporate social responsibility (CSR), managerial ownership, and leverage on earnings management, with audit quality as a moderating variable. The research sample consists of 17 companies consistently listed in the Jakarta Islamic Index (JII) during the 2021–2024 period, resulting in 68 firm-year observations. Secondary data were obtained from annual and sustainability reports, then analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews 12 software. The results show that CSR has a positive and significant effect on earnings management, while managerial ownership and leverage do not show significant effects. Furthermore, audit quality does not moderate the relationship between the independent variables and earnings management. The novelty of this research lies in examining the moderating role of audit quality in the relationship between governance mechanisms and earnings management in companies included in the JII, using data from the post-economic recovery period. This study contributes to strengthening empirical evidence regarding the limitations of the effectiveness of governance mechanisms in curbing earnings management practices in the context of the Sharia capital market.